Factors of Affecting The Quality of Achieving Health Centers on Patient Satisfaction at UPTD Langsa Baro Health Center in 2021 - Safrita; Thomson P Nadapdap; Miskah Afriani (International Archives of Medical Sciences and Public Health, 2022)
Achievement health centers are health centers that have succeeded in achieving achievements including high performance in accordance with the function of the health center. The purpose of this study was to determine the factors that influence the quality of health centers with achievement on patient satisfaction. The research design used in this study was an analytical survey with a cross sectional approach. The population of this study were 25,559 patients with a sample using accidental sampling technique of 100 people. Data collection methods are primary data, secondary and tertiary data. Analysis of the data used is a binary logistic regression test. The results showed that the physical evidence had a sig-p value of 0.042 < 0.05 and a sig-p reliability of 0.017 < 0.05, which means that it has an influence on the quality of achieving health centers, while guarantees, care and responsiveness are sig-p > 0.05 which means meaning that it does not have an effect on the quality of achieving health centers. It is hoped that it can be a reference for the community and for cadres at the Puskesmas to better understand the importance of service quality in accordance with the regulations of the ministry of health in order to improve the health services provided to patients to the maximum.